2015
DOI: 10.11648/j.ijmsa.s.2015040201.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorophyll and Anthocyanin on the Secondary Bonds of Poly Vinyl Chloride (PVC)

Abstract: This paper deals with the effect of natural pigments (chlorophyll and anthocyanin) on the secondary bonds in (poly vinyl chloride PVC), which play an important role in the physical and chemical behavior of it. Natural pigments extracted from plants by a simple method and blended with PVC powder in different ratio of natural pigments, and the properties of the blend were determined and compared. The extracted pigments were characterized by UV-visible spectroscopy and Fourier transform infrared spectroscopy (FTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Flavonoids have several subgroups, which include flavones, flavonols, flavanones, flavanonols, flavanols, and anthocyanins. Specifically, the FT‐IR spectra of extracted dyes in this study were well matched with FT‐IR spectra of anthocyanin shown in the literature . PMF, RTF, and JFL natural dye extracts exhibited all the characteristic peaks of the anthocyanin pigment, and they showed similar spectra.…”
Section: Resultssupporting
confidence: 83%
“…Flavonoids have several subgroups, which include flavones, flavonols, flavanones, flavanonols, flavanols, and anthocyanins. Specifically, the FT‐IR spectra of extracted dyes in this study were well matched with FT‐IR spectra of anthocyanin shown in the literature . PMF, RTF, and JFL natural dye extracts exhibited all the characteristic peaks of the anthocyanin pigment, and they showed similar spectra.…”
Section: Resultssupporting
confidence: 83%
“…Several major peaks at 3330, 2925, 2850, 1105, 1040 was observed from transmission spectrum. As shown in Figure 4, FTIR spectrum of the total pigments indicates the presence of high density chlorophyll pigment [16].…”
Section: Characterization Of Pigmentsmentioning
confidence: 94%
“…The broad peak at 3380 cm À1 was because of sugar vibrations and phenol O-H groups (Ahmed et al, 2013;Vankar and Shukla, 2011) which confirms the presence of phenols and aromatic group which tied H as an indicator of A and B rings of the anthocyanins pigment (aglycon) (Saati, 2015). The absorbance at 2,120 cm À1 and 2,000 cm À1 was attributed to C:C stretching vibrations (Sinha et al, 2012) while 1,700 cm À1 to C = O and 1,610 cm À1 to C = C groups (Ahmed et al, 2014). Further, the peaks observed at 1,050, 1,130, 1,220 and 1,360 cm À1 corresponds to the C-O-C bonds in the saccharide ring (Zhang et al, 2013).…”
Section: Fourier Transform Infrared Spectroscopy Analysis Of Sohiong Anthocyanins Concentratementioning
confidence: 96%